Reinforcing effect of lock stitching with small density on the tensile properties of composite T-joints. (August 2022) - Chen, Boran; Dong, Weiping; Zhao, Jiajiang; Zhao, Yuan; Wang, Linlin; Li, Xiping; Li, Mengjia; Chen, Puhui
Abstract: To examine the tensile properties of T-joints reinforced by traditional lock stitching with stitch spacing not smaller than 5 mm, tensile experiments are conducted and the reinforcing effect of stitching and Z-pinning is compared. Results show that both the location of the innermost column of stitching and stitch spacing have a remarkable influence on the tensile property of stitched T-joints. The maximum average peak load achieved is 44.2% by stitching. Although the diameter of the stitch is 24% thinner than that of a thick Z-pin, the maximum load capacity of stitched T-joints is 14.2% greater than that of Z-pinned T-joints. Graphical abstract: Highlights: Both the location of the innermost column and column spacing of stitching have a remarkable influence on T-joints. The maximum average peak load achieved was 44.2%. Stitching is superior to Z-pinning in terms of improving initial load drop, peak load, and stabilizing crack propagation.